IMAGINING TRANSFRONTERIAL SPACES IN MIA COUTO’S THE LAST FLIGHT OF THE FLAMINGO (Polifonia, 2013)
ABSTRACT: This paper reads Mia Couto’s novel O último vôo doflamingo, translated into English by David Brookshaw as The last flightof the flamingo, as postcolonial spaces of the subaltern, away from silenceinto rumorous fado, as it focuses on concepts of translingualism andinterculturality. In short, I investigate how the novel as a practice ofcultural translation accounts for a new society after Mozambique’s civilwar and how language in translation can help in its account.KEYWORDS: postcolonialism, interculturality, cultural translationRESUMO: Neste artigo, leio o romance O último voo do flamingo, deMia Couto, traduzido para o inglês por David Brookshaw como The lastflight of the flamingo, enquanto espaços pós-coloniais do subalterno,escapando ao silêncio e adentrando ao rumoroso fado, uma vez que elefoca em conceitos de translingualismo e interculturalidade. Sucintamente,investigo como o romance, enquanto uma prática de tradução culturalajuda a constituir uma nova sociedade após a guerra civil deMoçambique e como a língua traduzida contribui para isso.PALAVRAS- CHAVE: pós-colonialismo, interculturalidade, traduçãocultural